Shifting Language Ideology and Teaching Practice in Multilingual Class: Voices of Indonesian Lecturers in CLIL - Diyamon Prasandha; Lailatun Nurul Aniq (JEELS (Journal of English Education and Linguistics Studies), 2023)
Content and Language Integrated Learning (CLIL) has grown in popularity due to the idea that it may aid students in enhancing their foreign language proficiency. Previous studies have found that teaching a foreign language in a bilingual setting creates obstacles since students have fewer linguistic features in learning and teaching. While they investigated the significance of various perspectives in this process, this study explores language ideologies and practices in the multilingual background. It seeks the lecturer's voice who taught preparation courses for international students about his language ideologies and CLIL practices using different parameters of CLIL. This narrative study engaged guided dialogues and observations. We adopted Barkhuizen et al.’s (2014) thematic analysis for analyzing the data. It indicated that language ideologies emerged after framing the courses within the students' more comprehensive language ideological contexts, followed by a discussion of its relevance to classroom practice English is used to address gaps between individuals who might not share a common native language or a shared (domestic) identity and with whom English was the favored foreign language of communication. While he created a humanist course for students to use their broad vocabulary and grammar classes were nevertheless immersed in transitory language ideologies.